Reflections on the readings of Sundays and feasts: September-November 2021 - Sobb, Joseph (The Australasian Catholic record, 2021)
Today's gospel narrative, one of the few stories in the Gospel of Mark not found in any of the other gospels, has "locals", Gentiles, bring to Jesus a man who is deaf and with a speech impediment (presumably because of the deafness), not dumb. It is set in the region of Decapolis, a predominantly Gentile area. The preceding narrative (Mark 7:24-30) is set in Tyre, also a Gentile area. There, the pagan mother of a girl tormented by a demon comes to Jesus to beg his help. Her encounter and his response to her insistent pleas signal the breaking down of divisions and traditional boundaries-Gentile and Jew, outsider and insider, male and female. New relationships are coming into existence, and the old distinctions, illustrated in the dialogue between the woman and Jesus by the phrases, "children first" and "dogs under the table", are being rejected. This is central to the Good News when Jesus, after his baptism, began to proclaim the Good News of God in Galilee in a Jewish region: "the kingdom of God is at hand" (cf. Mark 1:14-15) or, as the Isaiah passage puts it, "here is your God!" (Lectionary: "your God is coming"). Mark's narrative in today's gospel reading continues on from that preceding narrative, and is again set in a Gentile region. The Good News of God's salvation is brought by Jesus, who crosses the boundaries to do so. The extract from James's letter is acknowledging that the Christian community has still to learn the full implications of their new-found faith. Faith in Jesus Christ excludes attitudes and activities which are inconsistent with his teaching and practice.